1997
DOI: 10.1055/s-2007-994149
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Magnesium Sulfate on the Development of Cystic Periventricular Leukomalacia in Preterm Infants

Abstract: To determine if magnesium sulfate has an effect on the development of cystic periventricular leukomalacia in preterm infants, this retrospective case control study was conducted. There were 23,382 infants born at three teaching hospitals in the metropolitan New York area from January 1992 to December 1994. Four hundred ninety-two infants met our entrance criteria. Criteria included a birth weight < 1750 g, survival to at least 7 days of life and at least one cranial ultrasound after 7 days of life. Infants exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
1
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 40 publications
(12 reference statements)
1
20
1
2
Order By: Relevance
“…This 50% reduction appeared achievable in view of much larger reductions of the risk of periventricular leucomalacia or cerebral palsy with magnesium sulphate reported in several observational studies. 6,8,9 Expecting that 20 and 1% of mothers would give birth to twins and triplets, respectively, meant that 906 mothers had to be included.…”
Section: Sample Sizementioning
confidence: 99%
See 1 more Smart Citation
“…This 50% reduction appeared achievable in view of much larger reductions of the risk of periventricular leucomalacia or cerebral palsy with magnesium sulphate reported in several observational studies. 6,8,9 Expecting that 20 and 1% of mothers would give birth to twins and triplets, respectively, meant that 906 mothers had to be included.…”
Section: Sample Sizementioning
confidence: 99%
“…1,2 Some WMI features, such as focal periventricular cysts, can be identified by routine cranial ultrasound scan (CUS) during the neonatal period. [3][4][5] In several human observational studies, prenatal administration of magnesium sulphate (MgSO 4 ) for tocolysis or preeclampsia was reported to be associated with lower neonatal mortality and lower risk of cerebral palsy in very-low-birthweight children, [6][7][8][9] even though these beneficial effects were not observed in other similar studies. [10][11][12] Three randomised trials were undertaken in recent years, one in Australia and New Zealand, one in France, and one in the United States, to assess the effectiveness of MgSO 4 in preventing neonatal mortality, perinatal cerebral injuries and/or cerebral palsy.…”
Section: Introductionmentioning
confidence: 99%
“…Desde el punto de vista cardiovascular se observa una disminución de la presión arterial y de la frecuencia cardíaca, no alterándose el gasto cardíaco debido al aumento compensatorio de la función ventricular 24 . Se ha observado que el Sulfato de Magnesio no produce daño en la sustancia blanca ni aumenta la incidencia de hemorragia intraventricular 25 ; de hecho se le ha atribuido una disminución en la frecuencia de leucomalacia y de parálisis cerebral en recién nacidos de bajo peso 26,27 . Es por esto que incluso se ha estudiado el uso de sulfato de magnesio como medida neuroprotectora en partos de pretérmino, con buenos resultados neonatales 28 .…”
Section: Efectos En El Recién Nacidounclassified
“…In 1995, a case-control study reported that sulfation in cases of extreme prematurity was probably associated with fetal neuroprotection effects 5 . Following this, other analyses were conducted on its applicability within obstetrics as a prevention for neurological lesions in extremely premature infants.Since only some of the subsequent studies showed that magnesium sulfate had a neuroprotective effect 6,7 , while others reported that this effect might not be sustainable [8][9][10] , new randomized studies were developed.A systematic review from the Cochrane Collaboration produced a meta-analysis of five randomized clinical trials that assessed the effect of neuroprotection provided through using magnesium sulfate in cases of prematurity 11 . This review showed that its use significantly reduced the risk of cerebral palsy, but did not increase fetal, neonatal, infant (up to two years of age) or maternal mortality.…”
mentioning
confidence: 99%
“…Since only some of the subsequent studies showed that magnesium sulfate had a neuroprotective effect 6,7 , while others reported that this effect might not be sustainable [8][9][10] , new randomized studies were developed.…”
mentioning
confidence: 99%